2004
DOI: 10.1152/ajpcell.00004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of type 2 inositol 1,4,5-trisphosphate receptors in cardiac myocytes from newborn mice

Abstract: The precise localization and role of inositol 1,4,5-trisphosphate (InsP(3)) receptors (InsP(3)Rs) in cardiac muscle cells are largely unknown. It is believed that waves and oscillations in cytosolic free calcium triggered by activation of InsP(3)Rs underlie modifications of cellular responses that lead to changes in gene expression in other cells. However, how changes in cytosolic calcium alter gene expression in cardiac cells is unknown. Moreover, it is unclear how changes in cytosolic calcium that alter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 55 publications
5
34
0
Order By: Relevance
“…Consistent with this model, it has been demonstrated that activation of IP 3 Rs in rat neonatal ventricular myocytes using a membrane-permeant IP 3 analogue or an α 1 -adrenergic agonist causes perinuclear Ca 2+ release events, and that blocking IP 3 R opening decreases hypertrophic growth in response to phenylephrine stimulation [109]. Similar findings were made using mouse neonatal cells stimulated with ET-1 and phenylephrine; nuclear-associated IP 3 Rs triggered nucleoplasmic Ca 2+ signals and hypertrophic gene transcription [157]. Further work is required to establish whether this scheme is relevant in vivo.…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with this model, it has been demonstrated that activation of IP 3 Rs in rat neonatal ventricular myocytes using a membrane-permeant IP 3 analogue or an α 1 -adrenergic agonist causes perinuclear Ca 2+ release events, and that blocking IP 3 R opening decreases hypertrophic growth in response to phenylephrine stimulation [109]. Similar findings were made using mouse neonatal cells stimulated with ET-1 and phenylephrine; nuclear-associated IP 3 Rs triggered nucleoplasmic Ca 2+ signals and hypertrophic gene transcription [157]. Further work is required to establish whether this scheme is relevant in vivo.…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 57%
“…However, the concept that IP 3 Rs impact specifically on nuclear Ca 2+ signaling is gaining momentum. Numerous recent reports examining Ca 2+ signaling in neonatal [103,108,109,157], atrial [71,72,137] and ventricular myocytes [140] have demonstrated specific effects of IP 3 -generating agonists or IP 3 itself on nucleoplasmic Ca 2+ signals. Coupling these data with the observations that IP 3 is necessary for some forms of hypertrophy [109,157,158] raises the possibility that IP 3 Rs are key regulators of cardiac myocyte gene transcription and fate.…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 99%
“…Together with the finding that inhibiting InsP 3 R opening prevented hypertrophic growth in response to phenylephrine stimulation (Luo et al, 2006), it is logical to conclude that phenylephrine promotes hypertrophy by activating perinuclear InsP 3 Rs and, consequently, causing nucleoplasmic Ca 2+ signals. Comparable observations have been made in cardiac cells stimulated with another InsP 3 -generating agonist, endothelin-1; InsP 3 Rs in close proximity to the NE triggered nucleoplasmic Ca 2+ signals and hypertrophic gene transcription, whereas EC-coupling did not (Garcia et al, 2004;Higazi et al, 2009). Although InsP 3 Rs conduct significantly less Ca 2+ and are expressed at levels that are ~100-fold lower than RyRs, the activation of InsP 3 Rs can clearly have a dramatic effect on gene transcription in cardiac myocytes owing to their specific impact on nuclear Ca 2+ .…”
Section: Measuring Nuclear Ca 2+ Signals: Key Considerationsmentioning
confidence: 61%
“…The presence of small InsP 3 -sensitive vesicular stores could help to explain the curious spotted distribution of nuclear InsP 3 R staining that is sometimes observed when using InsP 3 R-specific antibodies (particularly type-2-InsP 3 R-specific antibodies) (Garcia et al, 2004;Laflamme et al, 2002;Leite et al, 2003). If this is the case, these vesicular structures could represent nuclear InsP 3 -sensitive Ca 2+ stores that might operate independently of cytosolic Ca 2+ channels.…”
Section: Insp 3 Rs Ryrs and Naadprsmentioning
confidence: 99%
See 1 more Smart Citation